Postmodernisme: Antara Peluang dan Tantangan Bagi Filsafat dan Pendidikan - Didik Iskandar; Elly Purnamasari; Dase Erwin Juansah; Lukman Nulhakim (Mudir : Jurnal Manajemen Pendidikan, 2023)
Postmodernism is a source of understanding of the failure of modernist philosophers to advance human society. Because it fails to fulfill its mission to enable future human generations to advance intellectually and socially. The study aims to discuss history and development, the principles of postmodernism, as well as to examine the opportunities and challenges of post-modernism. This study is a qualitative descriptive study based on literature. The results of this study show that changes in postmodernism are inevitable, as emerging postmodern strategy models lead to new sustainable digital education transformation capabilities and new educational technologies. Therefore, society must respond to it through the cultivation of national values and the education of the individual in itself so that the consequences of the occurrence of the changes that occur can be minimized.